Diplomacy: theory & practice in Islam - Wang, Yong Bao (Ahmed Musa) (IIUM Press, 2009)
This book tries to elaborate on Islamic theories of diplomacy according to the practices and patterns set by Prophet Muhammad (peace be upon him) and his Companions. The theories include: the universal characteristics of Islam and the meaning and principles of diplomacy in Islam. A special attention is given to jihiid and the peaceful relations towards others. It is affirmed that the central theme in the Islamic external relations is PEACE. The book discusses some important issues, such as the necessary characteristics of diplomats and their functions during times of war and peace. Moreover, it elaborates applying diplomatic ways and means, providing privileges and immunities, conducting negotiations and concluding treaties in the field of international relations. The book also deals with some important traditional concepts, like dhimmah, amiin etc. The author has elucidated these concepts by discussing the arguments of the Muslim jurists and other experts in International Relations.